2019
DOI: 10.5114/pq.2019.83054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silicone gel versus Contractubex or corticosteroid phonophoresis for post-burn hypertrophic scars: a single-blind randomized controlled trial

Abstract: Introduction. Hypertrophic scars and keloids are physically and mentally disturbing, and can cause pain and itching. Various treatment is utilized to diminish or counteract scarring. The purpose of this study was to compare the effect of silicone gel, Contractubex gel, and corticosteroid phonophoresis for post-burn hypertrophic scars. Methods. A prospective, single-blind, randomized, controlled study with pretest-posttest design was performed; 45 patients aged 20-45 years with hypertrophic scars, 2-4 months po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…When topical silicone gel was compared with sheets, both were equally effective in lowering VSS scores (54% reduction for gel vs 52% reduction for sheets) and superior to onion extract gel, which yielded a 35% decrease in overall VSS score 35 . Wahba and colleagues 28 also showed a greater reduction in VSS scores in patients treated with silicone and phonophoresis vs those treated with onion extract and phonophoresis (62% vs 42% decrease in overall VSS score). However, silicone gel and onion extract gel were equally effective in reducing overall VSS and other scale scores 39 …”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…When topical silicone gel was compared with sheets, both were equally effective in lowering VSS scores (54% reduction for gel vs 52% reduction for sheets) and superior to onion extract gel, which yielded a 35% decrease in overall VSS score 35 . Wahba and colleagues 28 also showed a greater reduction in VSS scores in patients treated with silicone and phonophoresis vs those treated with onion extract and phonophoresis (62% vs 42% decrease in overall VSS score). However, silicone gel and onion extract gel were equally effective in reducing overall VSS and other scale scores 39 …”
Section: Resultsmentioning
confidence: 94%
“…The studies were subdivided into those which performed an intention‐to‐treat (ITT) analysis ( n = 15) and those which performed a per‐protocol analysis ( n = 19). Of the 15 studies with ITT analysis, only one study 39 was associated with a low risk of bias, while 5 18,23,28,30,40 and 9 17,20,25,29,31,33,35,37 studies were associated with moderate and high risk of bias, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition to combined treatment, we could also use methods like ultrasound or nanotechnology to improve the efficacy of single therapy. Wahba et al reported silicone gel phonophoresis outperformed steroid or onion extract phonophoresis for treating post‐burn hypertrophic scars . In a word, silicone gel as well as other silicone‐based products could serve as the “cornerstone” for various combined scar treatment, which is the future trend for scar management.…”
Section: Disscussionmentioning
confidence: 99%